Tantangan Pemolisian Hibrida dalam Menanggulangi Jaringan Penipuan Online: Studi Kasus dari Kabupaten Sidrap - Suarmita, I. G. N. Adi; Purnomo, Hadi (Al-Ishlah: Jurnal Ilmiah Hukum, 2023)
This research aims to examine the concept of hybrid policing in the context of crime prevention, specifically cyber fraud in Sidrap Regency. This research uses an empirical legal research method. All collected data is then qualitatively analyzed to describe the problem and answer the research objectives. The results show that the characteristics of cyber fraud in Sidrap Regency exhibit anonymity and disregard for geographical boundaries, with the primary motivation of the perpetrators being personal gain. They employ fake identities and compromised devices to execute their schemes, exacerbated by technological advancements, the public’s lack of awareness, and existing regulatory gaps. Therefore, it is recommended that the POLRI renew and adapt their policing model to be more responsive to the dynamics of cybercrime by implementing a hybrid policing approach. This involves active collaboration with community organizations in prevention efforts, which are expected to increase public awareness and strengthen the cyber security network. Additionally, developing an effective knowledge management system is advised, facilitating the exchange of information and strategies for handling cybercrime cases more efficiently. For researchers, it is crucial to examine further the social and psychological impacts of cybercrime on victims, which can contribute to forming a theoretical and practical foundation for a more holistic and victim-oriented approach to preventing and handling cybercrime in Sidrap Regency.